Centella asiatica in Oncology: An Ancient Herb with Modern Anticancer Promise - Sharmeen Shaikh; Pratiksha Salunkhe; Harshada Jadhav; Shoheb Shaikh (Pharmaceutical Science: New Insights and Developments Vol. 5, 2025)
Centella asiatica (L.) Urban, also known as Gotu Kola, has been traditionally used in Asian medicine for wound healing, neurological disorders, and skin conditions. In recent years, emerging scientific evidence has illuminated its remarkable anticancer properties. This chapter provides a critical review of the phytochemical constituents of Centella asiatica, their underlying mechanisms of action in various cancer types, in vitro and in vivo experimental findings, and the challenges associated with clinical translation. Emphasis is placed on the herb’s molecular targets and potential synergism with conventional chemotherapeutic agents (James & Dubery, 2009).